Immunohistochemical Expression of EGFR, NF-kB and Cyclin D1 in Sinonasal Inverted Papilloma and Squamous Cell Carcinoma - Pudji Rahaju; Rio Auricknaga Kintono; Ahmad Dian Wahyudiono; Arif Satria; Ferry Sandra (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Sinonasal inverted papilloma (SIP), a benign epithelial growth in the sinonasal region with epidermoid epithelial transformation, has been known for its invasiveness, recurrency, and its link with malignancy. Meanwhile sinonasal squamous cell carcinoma (SSCC) is an epithelial malignancy on squamous cells from the sinonasal region. Epidermal growth factor receptor (EGFR), Nuclear Factor kB (NF-kB), and Cyclin D1 are factors those might play important role in proliferation of SIP and SSCC. This research was conducted to investigate the expressions of EGFR, NF-kB and Cyclin D1 in SIP and SSCC.METHODS: A cross-sectional study by examining the EGFR, NF-kB, and Cyclin D1 immunohistochemical expressions of SIP and SSCC was conducted. Subjects whose blocks were used in this research, were diagnosed as SIP and SSCC at the Otorhinolaryngology-Head and Neck Surgery Clinic, Dr. Saiful Anwar General Hospital. Samples were selected, processed for inmmunohistochemistry, evaluated and statistical analyzed.RESULTS: Twenty-four SIP and 9 SSCC subjects with their paraffin blocks were selected. Clear immunohistochemical expressions of EGFR, NF-kB, and Cyclin D1 were observed for both SIP and SSCC. Significantly higher immunostaining levels of EGFR (45.6%, p=0.001) and NF-kB (42.2%, p=0.013) were observed in SSCC. Immunostaining levels of EGFR vs. NF-kB were moderately correlated (p=0.03, r=0.437), while the immunostaining levels of NF-kB vs. Cyclin D1 were strongly correlated (p=0.002, r=0.602).CONCLUSION: Expression of EGFR and NF-kB in SSCC were higher than the EGFR and NF-kB expression in SIP, suggesting that EGFR and NF-kB play important role in sinonasal malignancy.KEYWORDS: sinonasal, inverted papilloma, SCC, EGFR, NF-kB, Cyclin D1